Unbiased phishing detection using domain name based features - Shirazi, Hossein, author; Ray, Indrakshi, advisor; Malaiya, Yashwant K., committee member; Vijayasarathy, Leo R., committee member (Colorado State University. Libraries, 2018)
Internet users are coming under a barrage of phishing attacks of increasing frequency and sophistication. While these attacks have been remarkably resilient against the vast range of defenses proposed by academia, industry, and research organizations, machine learning approaches appear to be a promising one in distinguishing between phishing and legitimate websites. There are three main concerns with existing machine learning approaches for phishing detection. The first concern is there is neither a framework, preferably open-source, for extracting feature and keeping the dataset updated nor an updated dataset of phishing and legitimate website. The second concern is the large number of features used and the lack of validating arguments for the choice of the features selected to train the machine learning classifier. The last concern relates to the type of datasets used in the literature that seems to be inadvertently biased with respect to the features based on URL or content. In this thesis, we describe the implementation of our open-source and extensible framework to extract features and create up-to-date phishing dataset. With having this framework, named Fresh-Phish, we implemented 29 different features that we used to detect whether a given website is legitimate or phishing. We used 26 features that were reported in related work and added 3 new features and created a dataset of 6,000 websites with these features of which 3,000 were malicious and 3,000 were genuine and tested our approach. Using 6 different classifiers we achieved the accuracy of 93% which is a reasonable high in this field. To address the second and third concerns, we put forward the intuition that the domain name of phishing websites is the tell-tale sign of phishing and holds the key to successful phishing detection. We focus on this aspect of phishing websites and design features that explore the relationship of the domain name to the key elements of the website. Our work differs from existing state-of-the-art as our feature set ensures that there is minimal or no bias with respect to a dataset. Our learning model trains with only seven features and achieves a true positive rate of 98% and a classification accuracy of 97%, on sample dataset. Compared to the state-of-the-art work, our per data instance processing and classification is 4 times faster for legitimate websites and 10 times faster for phishing websites. Importantly, we demonstrate the shortcomings of using features based on URLs as they are likely to be biased towards dataset collection and usage. We show the robustness of our learning algorithm by testing our classifiers on unknown live phishing URLs and achieve a higher detection accuracy of 99.7% compared to the earlier known best result of 95% detection rate.
Keywords: domain name; phishing; biased datasets; phishing detection; machine learning